Analisis Keterampilan Berbicara Siswa Kelas Rendah pada Pembelajaran Bahasa Indonesia di SD Negeri Pasar Kemis III - Kurniawan, Eka Yulyawan; Awiria, Awiria; Fitriani, Rizky Mellynia (Lembaga Yasin AlSys, 2022)
Speaking skill is one of the language skills that must be mastered by students because speaking competence is the most important component in learning Indonesian language learning objectives, but most students consider speaking skill as a difficult skill according to second grade students of SD Negeri Pasarkemis III. The problem discussed in this study is how the students' speaking skills when completing pictorial conversations. This study is to describe the speaking skills of students in grade II at SD Negeri Pasarkemis III, Tangerang Regency. This research uses qualitative research with 27 students in class II and teachers in class II as the subject. The technique used to collect data is data reduction, data presentation and drawing conclusions. The conclusion of this study is that the things that cause a lack of speaking skills in students are due to shyness, lack of confidence, nervousness, and lack of practice and the learning process is still not using the media. Based on the analysis of the test results, there were 11 students with a percentage of 55% whose speaking skills were very poor, namely in the aspects of fluency, sentence structure, communicative/eye contact.